2008
DOI: 10.1111/j.1399-6576.2007.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain after hysterectomy

Abstract: Chronic pain is reported by 5-32% of women after hysterectomy. A guideline is proposed for future prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 25 publications
2
32
0
2
Order By: Relevance
“…According to Brandsborg et al (2008), a number of research studies indicate that surgery in itself has a serious risk for causing long-term and chronic pain. This occurs after a seriousprocedure like a thoracotomy or amputation, but even following minor surgical operations as well.…”
Section: Findings and Discussion:-mentioning
confidence: 99%
“…According to Brandsborg et al (2008), a number of research studies indicate that surgery in itself has a serious risk for causing long-term and chronic pain. This occurs after a seriousprocedure like a thoracotomy or amputation, but even following minor surgical operations as well.…”
Section: Findings and Discussion:-mentioning
confidence: 99%
“…The incidence of chronic pain after abdominal hysterectomy via Pfannenstiel is on the order of 10-15 % [68,69], so one could anticipate that chronic pain after cesarean delivery would be in the same range, given the similarity of the procedure. However, recent prospective studies have identified that the incidence and severity of reported pain after cesarean delivery is remarkably low…”
Section: Chronic Pain After Cesarean Deliverymentioning
confidence: 99%
“…Selv ved generell anestesi er det god rutine å bruke lokal anestesiinfiltrasjon i sårflater for postoperativ smertelindring (10). Trolig gir god smertelindring med lokal-eller regionalanalgesi redusert forekomst av kronisk nevropatisk smerte etter operasjoner (11).…”
Section: Valg Av Metode Og Kombinasjonerunclassified